Head–Eye Vestibular Motion Therapy Affects the Mental and Physical Health of Severe Chronic Postconcussion Patients - Carrick, Frederick Robert; Clark, Joseph F.; Pagnacco, Guido; Antonucci, Matthew M.; Hankir, Ahmed; Zaman, Rashid; Oggero, Elena (Frontiers in Neurology, 2017)
Context: There are approximately 1.8 to 3.6 million traumatic brain injuries in the United States annually, yet health care providers and medical researchers have yet to offer an effective, reliable evidence-based treatment for concussive brain injury. Objective: to test whether Head-Eye-Vestibular-Motion (HEVM) therapy is associated with decreased symptoms and increased function in postconcussive syndrome (PCS) patients that have been severely impaired for greater than six months after a mild traumatic brain injury (mTBI) . Our second objective was to test the use of the C3 Logix Concussion management system in identifying biomarkers and trends in the treatment of chronic PCS patients. Design: Retrospective Clinical Chart Review. Setting and participants: Tertiary Specialist Brain Rehabilitation Center. Interventions: All subjects underwent comprehensive neurological examinations including measurement of eye and head movement. The seven modules of the C3 Logix Comprehensive Concussion Management System were used for pre and post measurements of outcome of HEVM therapy. Methods: This study was a single center, retrospective review of records performed at our Institutional Brain Injury Clinic and conducted in accordance with the Declaration of Helsinki with equipoise. We utilized an objective validated measurement of physical and mental health characteristics of our patients before and after a one week HEVM rehabilitation program. We included only PCS patients that were disabled from work or school for a period of time exceeding 6 months after suffering a sports concussion. These subjects all were enrolled in a 5-day HEVM rehabilitation program at our Institutional Brain Center with pre and post C3Logix testing outcomes. Results: There was statistical and substantive significant decreases in PCS symptom severity after treatment and statistical and substantive significant increases in SAC scores. The outcomes were associated with positive changes in mental and physical health issues. Conclusion: HEVM therapy of 5 days duration is associated with statistical and substantive significant decreases of symptom severity associated with chronic PCS. This is a retrospective review and no control group has been included in this study. These are major limitations with retrospective reviews and further investigations with prospective designs including a randomized controlled study are necessary to further our understanding.